Respon Mekanik Komposit Hibrid Diperkuat Serat Karbon dan Serat Kaca Akibat Beban Impak Untuk Aplikasi Helm Keselamatan Kerja - Piliyang, Muhammad Yani; Amiruddin, Arfis; ., Indrayani; Ulana, Muhammad Indra (Fakultas Teknik UMSU, 2024)
Work safety helmets serve to protect the head from falling objects hitting the head directly and absorbing impact energy. To improve the performance of project helmets, innovations are made by using composite materials that combine the advantages of 2 types of fibers. This study aims to investigate the impact strength of hybrid composite materials using carbon fibers and glass fibers in an epoxy resin matrix and to make a prototype of a safety helmet. The manufacture of impact test specimens and prototype work safety helmets using the hand lay up method, using standar ASTM E23 05. The use of one type of fiber with a matrix:glass fiber or carbon fiber ratio of 50:50, and the use of a combination of two fibers with a matrix:glass fiber and carbon fiber ratio of 70:30. After that, charpy impact testing was carried out on the test specimens. The results obtained from impact testing show that the use of a combination of two carbon and glass fibers is able to withstand and absorb impact energy well.